Studied Speech and The Duchess of Malfi: The Lost Arts of Rhetoric, Memory, and Death - Rory Loughnane (Sillages Critiques)
In this article, Loughnane uses two key lines from the opening scene of Webster’s The Duchess of Malfi about the two brothers’ ‘studied speech’ to discuss how the play’s themes and ideas connect to a broader cultural preoccupation with practices of habitual preparation. Drawing on a wide range of early modern texts, Loughnane discusses the prevalence and proliferation of how-to manuals instructing readers how best to prepare for various activities and duties. In particular, he focuses upon manuals about conduct, memory, rhetoric, and death, connecting their aims and objectives to the tragedy that unfolds in Webster’s play. He situates the Duchess’s tragic outcome in her failure to heed her brothers’ warning, and in mistaking their contrived ‘studied speech’ for something without substance.